2017
DOI: 10.1002/pon.4532
|View full text |Cite
|
Sign up to set email alerts
|

Does depression decrease the moderating effect of self‐efficacy in the relationship between illness perception and fear of progression in breast cancer?

Abstract: The findings underscore the importance of considering the IP as determinants of FOP, as well as of self-efficacy and depression as the moderating factors in the relationship between IP and FOP, suggesting the need to enhance self-efficacy and depressive symptoms in order to compensate the negative impact of IP on FOP in breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…In line with our findings, illness perception positively associated with fear of progression (Shim et al, 2018). As the disease progresses, the exacerbation of patients' symptoms, the increase in economic cost and the accumulation of side effects will cause psychological, physiological and social impacts on patients (Maqhuzu et al, 2020; Yuan et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…In line with our findings, illness perception positively associated with fear of progression (Shim et al, 2018). As the disease progresses, the exacerbation of patients' symptoms, the increase in economic cost and the accumulation of side effects will cause psychological, physiological and social impacts on patients (Maqhuzu et al, 2020; Yuan et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…In a study conducted in New Zealand, on postmenopausal women with breast cancer undergoing chemotherapy, was reported a signi cant correlation between the worry of cancer recurrence and all domains of illness perception except personal control (26). Shim et al (2018) in an investigation among women with breast cancer in Korea reported that illness perception is a determinant of worry of cancer recurrence, and noted self-e cacy and depression as the moderators of the relationship between the illness perception and the worry of cancer recurrence (27). In another study on Japanese and Scandinavian women, the illness perception was signi cantly associated with the worry about cancer recurrence (28).…”
Section: Discussionmentioning
confidence: 99%
“…Depressive moods might affect a person’s belief to accomplish a desired behaviour or to achieve a target outcome (self-efficacy) 56. To control for the emotional state of the patients, we added a one-item Visual Analogue Scale on mood asking ‘how do you rate your mood during the last two weeks?’ 57…”
Section: Methods and Analysismentioning
confidence: 99%